(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
This paper focuses on developing a pedagogic roadmap to overcoming the challenges of delivering cyber security and forensics education in colleges and universities through distance learning during the COVID-19 pandemic. The research in this paper identifies the challenges associated with distance learning, teaching and assessment in the Sultan of Oman. The research evidence was gathered through educational practice at the Global College of Engineering and Technology (GCET), in the Sultanate Oman; and this research and pedagogic reflection acts as a case study for developing the pedagogic roadmap. The validation of evidence for the strategies suggested, and outcomes revealed and used at GCET, is through student feedback and questionnaires and satisfaction surveys. The adopted strategies enabled students to continue their learning during the pandemic. The strategies are validated with student satisfaction survey results, independently conducted by the college, which cover teaching and learning methods, assessment strategies, and overall satisfaction.